[PP.05.09] BLOOD PRESSURE CONTROL AMONG HYPERTENSIVE DIABETIC AND NON-DIABETIC IN A COHORT STUDY. (September 2016) - Sousa, A.C.; Jardim, P.C.; Jardim, T.; Barroso, W.; Araújo, Y.; Magalhães, F.G.; Arantes, A.C.; Costa, T.; Mikael, L.; Moreira, H.; Montello, M.; Sousa, W.; et al.
Abstract : Objective: To analyse the control of blood pressure among hypertensive patients with and without diabetes type 2, followed by eleven years in reference center. Design and method: A retrospective cohort study of hypertensive patients undergoing regular treatment. Diabetes mellitus was considered the exposure factor. The first assessment of the cohort was in 2004, intermediate follow-up in 2009 and the last in 2015; variables studied: gender, race, age, blood pressure, body mass index (BMI), and duration of treatment in specialized service. For blood pressure control among non diabetics values of <140/90 mmHg were considered and for diabetics values of <130/ 80 mmHg (strict goals) and <140/90 mmHg (overall goal) were considered. For the analysis of variables association was used chi-square test or Fisher exact test, with 5% significance level. Results: Included 139 hypertensive patients (diabetics: 55; non-diabetic: 84), with a mean time of hypertension treatment at the first assesment of 5.8 years. Most patients were females (75.5%) and the white race was predominant (55.8%). The average initial age of the cohort was 57.4 years (± 9.3). Hypertensive diabetics had lower control rates (23.6%/ 27.3%/ 29.1%) in all three periods compared to non diabetic patients (57, 1%/ 67, 9%/ 69, 0%), considering the strict goals (p < 0.001). But when used similar goals (<140/90) the difference among the groups disappeared (p > 0.05), with control rates of 47.3% / 61.8% / 60.0% in the respective periods of the exposed group. The average systolic blood pressure (SBP) remained similar between the groups over the follow-up (p > 0.05) and diastolic blood pressure (DBP) decreased significantly between the first and last segments in both groups (> 11 mmHg). The lack of blood pressure control was mainly associated with systolic blood pressure, and no association with any other variable analyzed. Conclusions: The presence of diabetes mellitus reflected in worse rates of blood pressure control when considered stricter targets for the control and this difference disappears with similar goals, regardless the the presence of diabetes.